An update on dıagnosıs and treatment of ANCA assocıated renal vasculıtıs - Turkmen, Kultigin; Ozer, Hakan; Tesar, Vladimir (International urology and nephrology, 2023)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitides are a group of diseases characterised by necrotizing inflammation of small vessels such as arterioles, venules, and capillaries. ANCA-associated vasculitides (AAV) are referred to as small vessel vasculitides. Three AAV subgroups, namely granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA) and eosinophilic GPA (EGPA), are defined according to clinical features. The most common disease with renal involvement in AAV is MPA Approximately 90% of patients with MPA have renal involvement. While this rate is 70-80% in GPA, less than half of EGPA patients have renal involvement. Untreated survival in AAVs is less than one year. With appropriate immunosuppressive therapy, the 5-year renal survival rate is 70-75%. Without therapy, the prognosis is poor but treatments, typically immunosuppressants, have improved survival, albeit with considerable morbidity from glucocorticoids and other immunosuppressive medications. Current challenges include improving the measures of disease activity and risk of relapse, uncertainty about optimal therapy duration and a need for targeted therapies with fewer adverse effects. In this review, we described the treatment of renal involvement in AAV in line with current studies.
Keywords: Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis; nemoci ledvin; ANCA-asociované vaskulitidy; granulomatóza s polyangiitidou; lidé; protilátky proti cytoplazmě neutrofilů; Antibodies, Antineutrophil Cytoplasmic; Immunosuppressive Agents; Granulomatosis with Polyangiitis; imunosupresiva; mikroskopická polyangiitida; Microscopic Polyangiitis; Churgův-Straussové syndrom; Kidney Diseases; Churg-Strauss Syndrome; Humans